Estimating and modeling charge transfer from the SAPT induction energy. Issue 26 (2nd August 2017) - Deng, Shi; Wang, Qiantao; Ren, Pengyu
Abstract : Recent studies using quantum mechanics energy decomposition methods, for example, SAPT and ALMO, have revealed that the charge transfer energy may play an important role in short ranged inter‐molecular interactions, and have a different distance dependence comparing with the polarization energy. However, the charge transfer energy component has been ignored in most current polarizable or non‐polarizable force fields. In this work, first, we proposed an empirical decomposition of SAPT induction energy into charge transfer and polarization energy that mimics the regularized SAPT method (ED‐SAPT). This empirical decomposition is free of the divergence issue, hence providing a good reference for force field development. Then, we further extended this concept in the context of AMOEBA polarizable force field, proposed a consistent approach to treat the charge transfer phenomenon. Current results show a promising application of this charge transfer model in future force field development. © 2017 Wiley Periodicals, Inc. Abstract : The charge transfer energy component has been one of the missing components in most current force fields. The authors report an approach to estimate the charge transfer energy from the SAPT induction energy and to model it using an atomic multipole moment model. The SAPT induction energy of water clusters were well reported using the new model.